Peningkatan Kelarutan Andrografolid dalam Fraksi Etil Asetat Herba Sambiloto (Andrographis paniculata Nees) Melalui Mikroenkapsulasi dengan Metode Semprot Kering - IDAH ROSIDAH; WAHONO SUMARYONO; SILVIA SURINI (JURNAL ILMU KEFARMASIAN INDONESIA, 2014)
Sambiloto (Andrographis paniculata Nees) is one of a medicinal plants containing andrographolide as its primary bioactive component, which is able to inhibit breast cancer cell proliferation. Andrographolide is a diterpene lacton that is sparingly soluble in water. The aim of this study is to improve the solubility of andrographolide in A. paniculata herbs ethyl acetate fraction by microencapsulation method prepared using spray drying. The ethyl acetate fraction of A.paniculata herbs was microencapsulated using PVP K30 and HPMC as the coating polymer in different ratios of ethyl acetat fraction and polymer (1:5; 1:7,5 and 1:10). Microspheres containing ethyl acetate fraction of A.paniculata herbs were evaluated their saturation solubility and in vitro dissolution in aquadest, pH 6.8 phosphate and pH 1.2 chloride medium. The result showed that the microencapsulation could increase the saturation solubility and dissolution rate of andrographolide as compared to the ethyl acetate fraction and andrographolide standard. Compared to the solubility of andrographolide from A. paniculata ethyl acetate fraction, the solubility of andrographolide on ethyl acetate fraction microspheres in aquadest, pH 6.8 phosphate and pH 1.2 chloride medium were increased approximately 23.42-39.34, 19.92-34.83 and 24.56-38.25 folds respectively. Moreover, compared to the solubility of andrographolide standard, the solubility of andrographolide on ethyl acetate fraction microspheres in aquadest, pH 6.8 phosphate and pH 1.2 chloride medium were increased approximately 16.99-28.53, 19.76-34.54 and 17.26-26.87 folds respectively.